Thailand’s Role as a Bridge between China and ASEAN - Zhang, Xizhen; Piyasirikul, Kampol; Liu , Changming; Li, Xinlei; Sun, Yunfei (Journal of Sinology (วารสารจีนวิทยา), 2017)
China's cooperation with ASEAN has become one of the highlights of China's foreign relations at that time. Considering the different closeness degree between ASEAN member states and China, China intends to seek pivot states in ASEAN which play a bridging role to promote mutual trust and integration between China and ASEAN, and form a community of shared interests and a community of common fate. Thailand has the basic conditions for becoming a pivot state. Of course, Thailand's role as a bridge cannot be overestimated, which still has some limitations. In order to help the bridging role to play further this report proposes the suggestions to both Chinese and Thai governments.